Implementasi Kepemimpinan Bamus terhadap Kenagarian Cingkariang - Febi Febriyanti; Hairul Anwar; Naflisa Siti Hafifah; Safuan Nada Fatmi (Yayasan Inovasi Akademi Nusantara, 2024)
The purpose of this study was to determine how the implementation of leadership in Bamus Cingkariang towards Nagari Cingkariang, how leadership is applied in Bamus Cingkariang both its impact on Nagari Cingkariang and the obstacles faced. The research method used is a qualitative research method using a descriptive approach. Data collection techniques are by observation and direct interview methods to the location of the study. The research was conducted in the Cingkariang village, Banuhampu District, Agam Regency, West Sumatra Province. Leadership is something that must exist in an organization, through the implementation of leadership, an organization will run well and will have an impact on positive things. The leadership in Bamus Cingkariang is democratic leadership that has the principle of deliberation and every member and community has the right to express opinions and aspirations in making policies and formulating problems. In the obstacles that hinder the work program, the solution that can be taken is to conduct socialization from Bamus and the village to the community about the existing regulations in order to create good implementation.